Participatory budgeting in the age of post-politics: examining the discourses of citizens and representatives of expert-political systems in three municipalities in Portugal - Santos, M.; Batel, S.; Gonçalves, M. E. (Portuguese Journal of Social Science, 2019)
In recent decades, a growing body of research has discussed and illustrated the so-called deliberative speak ‐ or how, despite representatives of the expert-political system agreeing with public participation in decision-making processes, in practice effective public participation barely occurs. To address this, new governing tools have recently been developed and implemented, such as participatory budgeting, particularly in societies in the Global North. We have also witnessed several profound sociopolitical and economic changes ‐ the post-political turn and localist agendas are all part and parcel of a new era of governance and political institutions that are being discussed increasingly by social scientists as questioning democracy. However, empirical analyses of if and how these changes are being appropriated ‐ reproduced and/or resisted ‐ in the everyday practices of expert-political systems and of citizens and what their consequences are for public participation have been neglected. To overcome that, this article will examine the discourses of citizens and representatives of expert-political systems about their participatory budgeting in three Portuguese municipalities.